The Analysis of Health Workers Roles in the Implementation of Community-Based Total Sanitation (STBM) - Taruli Rohana Sinaga; Sri Dearmaita Purba; Ivan Elisabeth Purba; Jasmen Manurung; Rahmat Alyakin Dachi; Rasmi Novita Sari Pardede (Jurnal Ilmu Kesehatan Masyarakat, 2025)
The 2020 Indonesian Health Survey reported that 74.4% of households in Indonesia had drinking water contaminated by E. coli bacteria. in response, the Indonesian government launched the Community-Based Total Sanitation (STBM) program. This study aimed to explore the role of health workers in the implementation of STBM Pillar I in work area of the Sentosa Baru Community Health Center (UPT). A qualitative study was conducted in Tegal Rejo Village, selected due to its high open defecation (OD) rate. Informants included sanitarian officers, village heads, health center heads, STBM cadres, and one community representative. Primary data were collected through in-depth interviews using interview guidelines and voice recorders, while secondary data were obtained from relevant agencies. Data were analyzed through data reduction, and the presentation in images and narrative descriptions. Results indicated that advocacy for the implementation of STBM Pillar I generated support from the village. Supporting factors were obtained from the shared goals between agencies in the implementation of STBM, while inhibiting factors were community characteristics that had unsupportive behavior or were ignorant. The triggering process began with fostering a positive atmosphere within the community through games, followed by agreeing on terms through discussions with the community, and culminating in a joint commitment. Recording and reporting were conducted manually by filling out the standarized forms. Health workers were expected to routinely report progress toward eliminating open defecation in each Sentosa Baru Community Health Center work area on the provided website and to continuously maintain and enhance their role as facilitator inpromoting proper defecation practices.